Effect of Service Capabilities on Performance of Banks – An Empirical Analysis - Misabpt; k, Rasheed; K, Saidalavi (International Journal of Psychosocial Rehabilitation, 2020)
Drawing upon Resource Based View (RBV of the firm this study seeks to elucidate how service capabilities affect performance in banking industry. The basic assumption of the study is that performance of banks can be enhanced to the extentthat banks are capable to deploy their resources and capabilities effectively for rendering banking services to their customers. Though there are several studies about internal capabilities and performance, this study stands unique by linking service capabilities with performance of banks. In this study a model is proposed that interlinks nine service capabilities with organizational performance based on empirical data collected from 351 managerial cadres of banks operating in India. The results reveal a strong support for the research proposition that service capabilities have significant and positive effect on performance of banks. The relative importance of all nine service capabilities and their effect on performance is also discussed. The findings of the study carry theoretical contributions for RBV based knowledge base and practical implications for banks working in competitive environments.